Analysis of Mathematical Reasoning Ability (MRA) with the Discovery Learning Model in Gender issues - Salam, Mohamad; Salim, Salim (Universitas Negeri Makassar, 2020)
This study examines students' mathematical reasoning based on Discovery learning models in terms of gender. This research was conducted at the SMPN 3 Kendari with quasi-experimental methods involving two classes with different treatments. The simple random technique is used to determine the class of research. Class VII. 6 (experimental class) consisted of 15 women and 11 men, while class VII.9 (control class) consisted of 15 men and 7 women. The instrument used was a student's mathematical reasoning ability test consisting of four items in the form of essays tested. Data processing using 2-way ANOVA with further tests using Scheffe. The conclusion obtained is that students are given a learning discovery model, the reasoning ability of male students excels in the ability to give mathematical problems verbally and in writing provided in the form of logical diagrams that contain existing data, perform mathematical manipulation related to the problem, and ensure validity as an argument, whereas women excel in the ability to draw conclusions based on relationships between mathematical concepts. The discovery learning model can increase students' mathematical penalties and overcome gender discussions.